FEELINGS OF WORKERS OF THE CLEANING STAFF OF A TEACHING HOSPITAL - Kawana Lopes Lanza; Benedita Gonçalves de Assis Ribeiro; Júlia Trevisan Martins; Caroline Vieira Cláudio Okubo; Maria José Quina Galdino; Maria Lúcia do Carmo Cruz Robazzi (Universidade Federal do Paraná, 2019)
Objective: To describe the feelings of pleasure and suffering of workers of the cleaning staff of a teaching hospital.Methodology: Descriptive and exploratory study, with a qualitative approach, with 24 cleaning workers of a teaching hospital in the state of Paraná. Data collection was performed through semi-structured interviews from April to July 2016 and the statements were submitted to content analysis. The theoretical assumption was psychodynamics of work with the use of Dejourian methodology.Results: The duality of pleasure and suffering was identified. The experiences of pleasure were related to teamwork and professional valuation and recognition. On the other hand, the experiences of suffering were related to lack of recognition and prejudice.Conclusion: It is concluded that both the managers and cleaners should implement actions to mitigate the feelings of suffering and maximize the experiences of pleasure, promoting the health of these workers.